Effects of six-week sprint interval or endurance training on calculated power in maximal lactate steady state - Hommel, J.; Öhmichen, S.; Rudolph, U. M.; Hauser, T.; Schulz, H. (Biology of Sport, 2019)
The purpose of the study was to evaluate and compare the influence of sprint interval training (SIT) and endurance training (ET) on calculated power in maximal lactate steady state (PMLSS) (influenced by the maximal lactate production rate ( VLamax) and maximal oxygen uptake ( VO2max)). Thirty participants were randomly assigned to the a) SIT, b) ET, or c) control group (n = 10 each). Each session consisted of four to six repetitions of 30 s all-out effort Wingate anaerobic tests (SIT) or 60 min cycling at 1.5 to 2.5 mmol·L-1 blood lactate (analysed every 10 min). Both groups performed training on three days per week, over a period of six weeks. To measure VLamax and VO2max, and to calculate PMLSS, sprint and ramp tests were performed at baseline and after two, four and six weeks of intervention. While SIT resulted in a significant reduction of VLamax (-0.08 ± 0.05 mmol·L-1·s-1, p=0.003) after two weeks and remained subsequently stable, VO2max(+2.6 ± 2.4 ml·min-1·kg-1, p = 0.044) and PMLSS (+25 ± 14 W, p=0.002) increased, but not before six weeks of SIT. After two weeks of ET, VLamax remained unchanged, but VO2maxincreased by increased by +2.9 ± 2.4 ml·min-1·kg-1, p=0.03, and after six weeks by 5.6 ± 3.5 ml·min-1·kg-1. The increase of PMLSS was significant after four weeks of ET (+16 ± 14 W, p=0.036) and increased to +32 ± 17 W after six weeks. Comparison of SIT and ET revealed no significant differences for VLamax, VO2maxor PMLSS after six weeks. The control group remained stable in all parameters. In both exercising groups there was a significant improvement of the calculated PMLSS due to different influences of VLamax and VO2max.